2021
DOI: 10.3389/fneur.2021.724705
|View full text |Cite
|
Sign up to set email alerts
|

First Experience of Three Neurovascular Centers With the p64MW-HPC, a Low-Profile Flow Diverter Designed for Proximal Cerebral Vessels With Antithrombotic Coating

Abstract: Background: In the last decade, flow diversion (FD) has been established as hemodynamic treatment for cerebral aneurysms arising from proximal and distal cerebral arteries. However, two significant limitations remain—the need for 0.027” microcatheters required for delivery of most flow diverting stents (FDS), and long-term dual anti-platelet therapy (DAPT) in order to prevent FDS-associated thromboembolism, at the cost of increasing the risk for hemorrhage. This study reports the experience of three neurovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…This is contrasted by significantly lower complication rates reported by large-volume neurovascular centers ( 12 14 , 21 ) and underlines the importance of proper patient selection, treatment technique, and a patient-tailored, appropriate DAPT regimen ( 18 , 22 ). The results of the latter studies are in line with our experiences with the use of flow-diverting stents for treatment of bifurcation aneurysms, showing good safety and efficacy with low complication rates, especially when applying flow-diverting stents with anti-thrombotic coatings ( 11 , 23 ).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This is contrasted by significantly lower complication rates reported by large-volume neurovascular centers ( 12 14 , 21 ) and underlines the importance of proper patient selection, treatment technique, and a patient-tailored, appropriate DAPT regimen ( 18 , 22 ). The results of the latter studies are in line with our experiences with the use of flow-diverting stents for treatment of bifurcation aneurysms, showing good safety and efficacy with low complication rates, especially when applying flow-diverting stents with anti-thrombotic coatings ( 11 , 23 ).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, the most appropriate DAPT combination and its optimal duration must be determined in context of indirect flow diversion. As reflected by recent reports, the choice of the anti-platelet medication is a crucial determinant of the rate of ischemic and hemorrhagic complications in flow diversion ( 26 ) and may influence the time point of aneurysm occlusion as well ( 11 ). From a current perspective, the combination of ASA and Ticagrelor appears to be superior to ASA and Clopidogrel ( 22 ), although single anti-platelet therapy (SAPT) with Prasugrel only has shown promising results in combination with anti-thrombotically covered flow-diverting stents ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the use of flow diverters or intracranial stents to treat cerebral aneurysms, dual antiplatelet therapy is necessary to prevent stent-related thromboembolic events. Recently, an anti-thrombotic polymer coating has been developed for coating a flow diverter (the p48MW HPC), and this coated flow diverter allows application of a single antiplatelet function medication for endovascular treatment of cerebral aneurysms, especially ruptured ones ( 34 36 ). Recent exploring studies have proved that deployment of this coated flow diverter is able to decrease thrombogenicity safely and effectively, and achieves good early aneurysm occlusion rates in cerebral aneurysms in the proximal intracranial circulation, complex bifurcation aneurysms in the anterior and posterior circulation, and distally located cerebral aneurysms even though further larger comparative studies are essential to confirm these outcomes and optimize the perioperative antiplatelet treatment ( 34 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies were conducted in Germany, 9,11,14,[22][23][24][25][26][27][28] 2 in France, 8,29 3 in Belgium 12,13 (1 shared a location with Portugal 30 ), 2 in Mongolia, 31,32 and the remaining in Argentina, 25 Bulgaria, 33 and Italy. 34 Details about the location of the studies are shown in Fig.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%